NORMA SOSIOMATEMATIK:HUBUNGAN ANTARA INTERAKSI SOSIAL MAHASISWA DAN HASIL BELAJAR MATEMATIKA - Mohammad Archi Maulyda; Dyah Indraswati; Setiani Novitasari; Deni Sutisna; Ida Ermiana (Universitas Majalengka, 2021)
The social interactions that occur between individuals in mathematics are called sociomatematics. Sociomatematic norms are rules derived from mathematical values that are brought into a social context. Sociomatematic norms are seen as being able to improve students' understanding. The main focus of this research are, (1) Analyzing social content in Elementary School Mathematics Learning courses; (2) Describing the social interaction process on the research subject; and (3) Describe the relationship between social interactions and mathematics learning outcomes. This type of research is quantitative with a descriptive approach. The research subjects were 100 PGSD students. The data collection technique used a survey method and the analysis of the results of the student mathematics examination. Data analysis used simple linear regression analysis. From the research, the results obtained: (1) Mathematical content in the lecture process has been raised by the lecturer. The lecture system in the form of group discussions can improve students' communication skills, courage and cooperation. (2) An overview of student social interactions can be modeled. The social interaction model shows that social interaction can take the form of associative and dissociative. (3) There is a relationship between social interaction and mathematics learning outcomes. This relationship is quite strong, and social interactions have an effect on student mathematics learning outcomes.